Modelo matemático para medir el rendimiento de la producción del mango kent (Mangifera indica ‘Kent’) de la región Piura destinado a la exportación 2018 -2022 - Lopez, Claudia (2024)
This study focuses on the creation of a rigorous mathematical model that evaluates the performance of Kent mango (Mangifera indica ‘Kent’) production in the Piura region during the period 2018-2022, especially with regard to its export. Advanced quantitative analysis and specific metrics are used to quantify efficiency and productivity in the mango industry. The proposed model provides an essential tool for actors involved in the mango supply and export chain, allowing more informed and strategic decision making, which is why the research is based on solid data and precise mathematical calculations. Likewise, this scientific approach is crucial to optimize the production and export of Kent mangoes in the Piura region, contributing to the sustainable development of the industry.